2020
DOI: 10.1103/physrevresearch.2.033036
|View full text |Cite
|
Sign up to set email alerts
|

Exchange interaction of hole-spin qubits in double quantum dots in highly anisotropic semiconductors

Abstract: We study the exchange interaction between two hole-spin qubits in a double quantum dot setup in a silicon nanowire in the presence of magnetic and electric fields. Based on symmetry arguments we show that there exists an effective spin that is conserved even in highly anisotropic semiconductors, provided that the system has a twofold symmetry with respect to the direction of the applied magnetic field. This finding facilitates the definition of qubit basis states and simplifies the form of exchange interaction… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 79 publications
2
20
0
Order By: Relevance
“…2b). The optimal SOI saturates to v * = 2.56 2 /ml E ≈ 25 meV nm×E 1/3 when w 3l E ≈ 24 nm×E −1/3 ; this condition is easily met in state-of-the-art devices, where w ∈ [15,30] nm and E 1 V/µm [1]. We remark that the case w l E also describes inversion layers.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…2b). The optimal SOI saturates to v * = 2.56 2 /ml E ≈ 25 meV nm×E 1/3 when w 3l E ≈ 24 nm×E −1/3 ; this condition is easily met in state-of-the-art devices, where w ∈ [15,30] nm and E 1 V/µm [1]. We remark that the case w l E also describes inversion layers.…”
mentioning
confidence: 84%
“…acting on the Kramer partners | ↑ and | ↓ . Here, we introduce a matrix gij = δ ij (α i − β i p 2 y / 2 ) of wire gfactors, which is diagonal because of symmetry [27,30] and includes momentum dependent corrections β i [14,15]. The orbital gap ωy differs from the frequency ω y because of the effective mass m, i.e.…”
mentioning
confidence: 99%
“…Generally, there are further terms possible, such as a diagonal term linear in k y or an off-diagonal term quadratic in k y . However, these terms are zero in the isotropic LK Hamiltonian [52]. This effective model works well in different geometries, however in this section we restrict ourselves to the analysis of NWs with square cross-section.…”
Section: Effective G-factor and Effective Massesmentioning
confidence: 99%
“…A similar route has recently been used to investigate the dynamics of a pair [ 25 , 26 , 27 , 28 , 29 , 30 , 31 ] or a chain [ 32 , 33 ] of coupled spins (also greater than ) subjected to time-independent and time-dependent [ 34 , 35 , 36 ] external magnetic fields. Symmetry arguments have also been exploited to elegantly bring to light intriguing dynamic features of physical systems living in Hilbert spaces of infinite dimensions [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. In Section 4 it is demonstrated that the time evolution of the two dipolarly coupled spins nests a qutrit subdynamics governed by a Hamiltonian model that is explicitly derived.…”
Section: Introductionmentioning
confidence: 99%